Handball tactics and game model - da Silva , Luvanor Santana; dos Santos, Francisco Xavier; Melo, Wilson Viana de Castro; Leão, Iberê Caldas Souza (Seven Editora, 2024)
The objective of this study was to discuss the process of teaching and training tactics in handball, in order to enable a game model for the teaching of this sport. It is a descriptive and exploratory narrative review of handball with regard to the use of tactical elements. The databases of Bireme, Pubmed, Scielo and SPORTDicus were used. The search period for studies was from 2013 to 2023. A total of 1,142 studies were found, after analysis of which 241 were eligible and only 19 were able to meet the research criteria. It should be noted that training should not be based only on traditional teaching and training methods. From the analysis carried out with this study, the learning of defensive and offensive tactical fundamentals in handball, facilitates the teaching-learning-training process of the modality, providing a possible construction of a game model. DOI:https://doi.org/10.56238/sevened2024.026-004